Linguistic and philological hypothesis on OPr. III 101, 18 ainawijdi - Dini, Pietro U. (Baltistica, 2019)
The OPr. form ainawijdi is attested in the liturgical supplement of the Marriage Booklet (Traubüchlein) of Martin Luther’s Enchiridion. Traditionally it is mostly understood as an adverb with adversative meaning (cf. Endzelīns: Latv. tomēr, taču; Mažiulis: Lith. vienókiai, tačiau).In this paper a new interpretation of the form ainawijdi is given, based on a newly accomplished comparative, philological and semantic investigation of the passage in which the form is used.
Keywords: Baltic languages; Old Prussian; Philology; Enchiridion; ainawijdi